Pulmonary Congestion Due to Right and Left Heart Output Mismatching: A Case Report and Literature Review - Yuan, Jing; Li, Yongjun; Sun, Jie (Frontiers in Physiology, 2021)
We report a new pulmonary circulation model during cardiopulmonary bypass that is able to cause pulmonary congestion but without left heart failure. This kind of congestion is characterized with right and left heart output mismatching. The pathophysiological mechanism, clinical manifestations, diagnosis, differential diagnosis, and treatment of this pulmonary congestion is reviewed in the following paper.